2017
DOI: 10.1002/slct.201702173
|View full text |Cite
|
Sign up to set email alerts
|

Palladium-Catalyzed C-H Functionalization of Amido-Substitued 1,4-Napthoquinone in the Presence of Amines toward the Formation of Pyrroles and Imidazoles

Abstract: Transition metal‐catalyzed ortho‐ C−H functionalization of amido‐substituted 1,4‐naphthoquinone, 3, in the presence of Pd(OAc)2 and tertiary amines led to the formations of 4 with newly generated pyrrole rings. Similar reactions were carried out with primary amines and yielded 5, having imidazole rings, as well as amination products 6. In the cases of reacting with secondary amines, the route for the formations of 4‐like, rather than 5‐type, products were prevailed. As revealed from the crystal structures of 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 62 publications
1
6
0
Order By: Relevance
“…The crude product was purified by column chromatography by using ethyl acetate/petroleum ether mixture as an eluent. [14] (3 aa)…”
Section: General Procedures For Synthesis Of Indoloquinonesmentioning
confidence: 99%
See 1 more Smart Citation
“…The crude product was purified by column chromatography by using ethyl acetate/petroleum ether mixture as an eluent. [14] (3 aa)…”
Section: General Procedures For Synthesis Of Indoloquinonesmentioning
confidence: 99%
“…[13] Later, in 2017, Chen and Hong utilized trimethylamine as a one carbon-donor to the 2amidonaphthoquinone to construct pyrrolonaphthoquinone-core through Pd(OAc) 2 -catalyzed CÀ H functionalization. [14] Although these methods are of synthetic importance, using an expensive catalyst (sometimes stoichiometric amounts) and limited substrate scope often vitiates their synthetic utility. Thus, developing an efficient, less expensive, sustainable and environmentally friendly catalytic system for the practical synthesis of benzo[f]-indole-4,9diones from the readily available starting materials with high atom economy is desirable.…”
Section: Introductionmentioning
confidence: 99%
“…The absorption spectra of 2-substituted naphth[1,2- d ]imidazoles ( IM2 – IM7 ) showed two absorption bands in the ultraviolet region, corresponding to the π→π* transition of the substituent at the carbon C2 of the naphthoimidazole ring (~314 nm) and of the imidazole ring (~363 nm) [ 25 , 26 , 27 ] ( Table S1 ).…”
Section: Resultsmentioning
confidence: 99%
“…The first route is an intramolecular cyclization process that leads to the formation of a nonsubstituted benzene ring in XI and eventually to the formation of 3b through procedures stated elsewhere. [31] The second route is a more complicated cyclization process involving a Diels-Alder-type reaction between VI and (E)-N,N-dibutylbut-1-en-1-amine. This process eventually bought about the formation of a diethyl-substituted benzene ring in XII.…”
Section: Proposed Mechanism For the Formations Of 3b And 3dmentioning
confidence: 99%
“…[30] Our previous works have demonstrated a new and fascinating pathway for creating a pyrrole ring from the reactions of amido-substituted naphthoquinones with tertiary amines, which led to the formations of 3-type products (Scheme 2). [31,32] Interestingly, the newly added di-carbon fragment in the pyrrole ring of the 3type products is in fact originally from the used amine, rather than the former amido-group of 2a_NQ (or 2b_NQ). It is clearly shown that the tertiary amine plays dual roles here, both as a base and reactant.…”
Section: Introductionmentioning
confidence: 99%